Arin’s Postre / Nur Arissya Putri Mohd Zamzam and Nurin Amirah Mohammad Azhar - Mohd Zamzam, Nur Arissya Putri; Mohammad Azhar, Nurin Amirah (2022)
Arin’s Postre is a bakery business that are sell Mamasab Bakery product. We choose a general name so that we can expand our career as a dropshipper not only for one brand. Our main goal is to be the best dropshipper that provides prompt and excellent services to meet the needs of the customer. We chose to sell Mamasab Bakery goods because they provide delicious and delectable goods at reasonable prices that will please our customers. Arin’s postre business members consist of Nur Arissya Putri Binti Mohd ZamZam and Nurin Amirah Binti Mohammad Azhar. On June 1, 2022, we launched our company online. Our primary platform is Facebook, where we draw customers with different marketing images (hard-sell) that also include some knowledge (soft-sell). According to customer reviews, they were happy with our services, which included helping them choose a cake and ensuring that it would arrive on time. We sell cake, cupcakes, and cookies made by Mamasab Bakery. In the meantime, we made the decision to concentrate on cake sales and will continue to advertise other products in the future. Arin’s postre target market are Kuala Lumpur and Selangor community, dessert lover and young aged 18-40 years old people.On the other hand, to compete with other dropshipper of Mamasab Bakery, we will provide online member card to the loyal customer to get lower price. This is our unique value to ensure that our customers will come back to us for future orders. For the first month of operation, we successfully made a sale of RM 80. We will broaden our marketing efforts in the future to include platforms like Instagram, Twitter, and Telegram in order to reach more people.